HMM-based speech synthesis with an acoustic glottal source model - Cabral, Joao; Richmond, Korin; Yamagishi, Junichi; Renals, Steve (My University, 2009)
A major cause of degradation of speech quality in HMMbased speech synthesis is the use of a simple delta pulse signal to generate the excitation of voiced speech. This paper describes a new approach to using an acoustic glottal source model in HMM-based synthesisers. The goal is to improve speech quality and parametric flexibility to better model and transform voice characteristics.
The First Young Researchers Workshop in Speech Technology
Keywords: HMM-based speech synthesis; LF-Model; Glottal spectral separation; Creative Technologies; Speech synthesis; VOICE SOURCE